Global continental and marine detrital εNd: an updated compilation for use in understanding marine Nd cycling - Robinson, S; Ivanovic, R; Van de Flierdt, T; Blanchet, CL; Tachikawa, K; Martin, EE; Cook (Falco), CP; Williams, T; Gregoire, L; Plancherel, Y; Jeandel, C; Arsouze, T (Chemical Geology, 2021)
Understanding the role of sediment-water interactions in the oceanic cycling of neodymium (Nd) isotopes is essential for its reliable use as a modern and palaeoceanographic tracer of ocean circulation. However, the exact processes that control Nd cycling in the ocean are poorly defined and require an up-to-date knowledge of the sources, sinks and transformation of this tracer to and within the ocean (e.g. as per the GEOTRACES core mission). We propose a considerable improvement of Nd-source identification by providing an extensive and up-to-date compilation of published terrestrial and marine sedimentary Nd isotopic measurements. From this database, we construct high resolution, gridded, global maps that characterise the Nd-isotopic signature of the continental margins and seafloor sediment. Here, we present the database, interpolation methods, and final data products. Consistent with the previous studies that inform our compilation, our global results show unradiogenic detrital Nd isotopic values (εNd ≈ -20) in the North Atlantic, εNd values of ≈ -12 to -7 in the Indian and Southern Ocean, and radiogenic values (εNd ≈ -3 to +4) in the Pacific. The new, high-resolution interpolation is useful for improving conceptual knowledge of Nd sources and sinks and enables the application of isotope-enabled ocean models to understand targeted Nd behaviour in the oceans. Such applications may include: examining the strength and distribution of a possible benthic flux required to reconcile global Nd budgets, establishing the potential use of Nd isotopes as a kinematic tracer of ocean circulation, and a general quantification of the non-conservative sedimentary processes that may contribute to marine Nd cycling.